Cooled radiofrequency ablation versus cryoneurolysis of the genicular nerves for the symptomatic pain management in knee osteoarthritis: a study protocol of a prospective, randomized, single-blinded clinical trial - A. Panagopoulos; P. Tsiplakos; K. Katsanos; P. Antzoulas; J. Lakoumentas (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background Cooled radiofrequency ablation (CRFA) and cryoneurolysis (CRYO) are two novel methods of genicular neurolysis to relief pain in symptomatic knee osteoarthritis (KOA). In this study, the two methods will be compared, giving us the opportunity to investigate their efficacy, safety and complications. Methods In this prospective randomized trial 70 patients with KOA will be recruited using a diagnostic block of four genicular nerves. Two groups will be created through software randomization: a CRFA group (35 patients) and a CRYO group (35 patients). The target of the interventions will be four genicular nerves; the superior medial, superior lateral, inferior medial, as well as the medial (retinacular) genicular branch from vastus intermedius. The primary outcome of this clinical trial will be the efficacy of CRFA or CRYO at 2-, 4-, 12-and 24-weeks post-intervention using the Numerical Rating Pain Scale (NRPS). The secondary outcomes are the safety of the two techniques, as well as the clinical evaluation using the Knee Injury and Osteoarthritis Outcome Score (KOOS), the Oxford Knee Score (OKS), and the 7-point scale of Patient Global Impression of Change (PGIC). Discussion These two novel techniques can block pain transmission through genicular nerves in different ways. In contrast to cryoneurolysis, the CRFA method has been well documented in the past. This is the first clinical trial to compare CRFA vs CRYO and draw conclusions about their safety and efficacy. Trial registration ISRCTN87455770 [ https://doi.org/10.1186/ISRCTN87455770 ]. Registered 29/3/2022, first patient recruited 31/8/2022.